How physical exercise enhances life satisfaction in Chinese senior college students: mediating roles of self-efficacy and resilience - Yu, Huasen; Li, Xuening; Yu, Xin; Fusheng, Liang; Li, Liqiang; Yang, Yuhang; Wu, Jin (Frontiers in Psychology, 2025)
ObjectiveThis study explored the relationship between physical exercise and life satisfaction among senior college students by focusing on the mediating roles of self-efficacy and resilience, thereby providing theoretical support for the mental health benefits of physical exercise for senior students.MethodsA survey was conducted with 600 senior students from 10 universities using the physical exercise rating, life satisfaction, self-efficacy, and resilience scales. Data analysis was performed using SPSS 23.0 for descriptive statistics, correlation analysis, and reliability and validity assessments. In addition, AMOS software (version 24.0) was used to construct a structural equation model to test the hypothesized pathways and the effects of potential mediating variables.ResultsThere were significant positive correlations among the variables of physical exercise, life satisfaction, self-efficacy, and resilience (r = 0.11–0.62, all p < 0.01). The structural equation model revealed that resilience fully mediated the relationship between physical exercise and life satisfaction among senior students (95% CI: 0.105–0.243), while self-efficacy did not mediate this relationship (β = 0.02, p = 0.77). However, a chain mediating effect involving self-efficacy and resilience was observed between physical exercise and life satisfaction (95% CI: 0.127–0.235).ConclusionEnhanced physical exercise can improve self-efficacy and resilience among senior college students, thereby increasing their life satisfaction.